(3z-1)-(z+2)=15

Simple and best practice solution for (3z-1)-(z+2)=15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3z-1)-(z+2)=15 equation:


Simplifying
(3z + -1) + -1(z + 2) = 15

Reorder the terms:
(-1 + 3z) + -1(z + 2) = 15

Remove parenthesis around (-1 + 3z)
-1 + 3z + -1(z + 2) = 15

Reorder the terms:
-1 + 3z + -1(2 + z) = 15
-1 + 3z + (2 * -1 + z * -1) = 15
-1 + 3z + (-2 + -1z) = 15

Reorder the terms:
-1 + -2 + 3z + -1z = 15

Combine like terms: -1 + -2 = -3
-3 + 3z + -1z = 15

Combine like terms: 3z + -1z = 2z
-3 + 2z = 15

Solving
-3 + 2z = 15

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 2z = 15 + 3

Combine like terms: -3 + 3 = 0
0 + 2z = 15 + 3
2z = 15 + 3

Combine like terms: 15 + 3 = 18
2z = 18

Divide each side by '2'.
z = 9

Simplifying
z = 9

See similar equations:

| 1.75x+0.65=10 | | 1.75-0.65x=10 | | -3e=9e+7 | | 2x1/2=9/8 | | X^2-12x-3=14 | | 3ax+1=16 | | 0.4=.40 | | 5y=16[8] | | 36=2x+y | | z/7-3=2 | | x^2-33= | | -8(6x-2)+7(7x-7)-7=6-2 | | u/11=6 | | 11w=8470 | | -[7x+(6x+1)]=4-(5x+8) | | 6x^2-12x-51=-3 | | t+12=24 | | -4ln(x)+2x+6=0 | | 3tanx-5=4 | | 5k^2+12k+4= | | cos^2x+4cosx-5=0 | | 1000000/5-100000*3/30/2-470 | | 4x^2+6x-28=0 | | 10x^2-15x-70=0 | | 4x^2-30x+54=0 | | 12x^2-116x+224=0 | | 15x^2-25x-40=0 | | 25x^2+180x+180=0 | | X=3-31/30 | | 21x^2-153x-120=0 | | 25a^2+20a-60=0 | | 4/5*25/8 |

Equations solver categories